Enzyme‐Catalyzed Meinwald Rearrangement with an Unusual Regioselective and Stereospecific 1, 2‐Methyl Shift. Issue 28 (24th May 2022) - Xin, Ruipu; See, Willy W. L.; Yun, Hui; Li, Xirui; Li, Zhi
Abstract: The Meinwald rearrangement is a synthetically useful reaction but often lacks regioselectivity and stereocontrol. A significant challenge in the Meinwald rearrangement of internal epoxides is the non‐regioselective migration of different substituents to give a mixture of products. Herein, an enzyme‐catalyzed regioselective and stereospecific 1, 2‐methyl shift in the Meinwald rearrangement of internal epoxides is reported. Styrene oxide isomerase (SOI) catalyzed the unique isomerization of internal epoxides through 1, 2‐methyl shift without 1, 2‐hydride shift to give the corresponding aldehydes and a cyclic ketone as the sole product. SOI‐catalyzed isomerization showed high stereospecificity, fully retaining the stereoconfiguration. The synthetic utility of this enzymatic Meinwald rearrangement was demonstrated by its incorporation into three new types of enantioselective cascades, to convert trans ‐β‐methyl styrenes into the corresponding R ‐configured alcohols, acids, or amines in high ee and yield. Abstract : A highly regioselective and stereospecific enzyme‐catalyzed Meinwald rearrangement of internal and cyclic epoxides through a 1, 2‐methyl shift gave aldehydes or ketones as the sole product with enantio‐retention. The unique isomerization was incorporated into enantioselective cascades, providing novel access to chiral alcohols, acids and amines from readily available trans ‐β‐methylstyrenes.